Implementasi Strategi Pemasaran Instagram terhadap Peningkatan Penjualan Produk Lokal: Studi Kasus pada Toko JajanKoe di Cilacap - Cermansyah, Trie Yulie; Nurwibowo, Fajar; Mubarak, Zulfikar Yusya (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to explore how local businesses, particularly Toko JajanKoe in Cilacap, utilize Instagram as a strategic digital marketing platform to enhance product sales. Employing a descriptive qualitative approach, data were collected through in-depth interviews, observation of Instagram activities, and documentation analysis. The findings reveal that Instagram features such as Stories, Reels, and Live have significantly increased customer engagement and brand visibility. However, limitations such as resource constraints and algorithmic changes remain major challenges. This research contributes to the practical understanding of how micro-businesses can adapt digital marketing strategies effectively.